Carcinoma ani á Íslandi 1987-2003 : lýðgrunduð rannsókn - Halla Viðarsdóttir; Páll Helgi Möller; Jakob Jóhannsson; Jón Gunnlaugur Jónasson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2006)
Hægt er að lesa greinina í heild sinni með því að smella á hlekkinn View/Open OBJECTIVE: Anal cancer is a rare disease. The aim of this study was to describe anal cancer in Iceland in 1987-2003 with respect to incidence, histologic type, treatment, recurrence rate and survival. MATERIAL AND METHODS: This is a retrospective study in which all malignant anal tumours diagnosed in Iceland in the period 1987-2003 were reviewed with respect to patient outcome. Information was obtained from hospitals registers. All histological material was reviewed by a consultant histopathologist (JGJ). This is a nationwide, population-based study of malignant tumours of the anal region. RESULTS: From 1987-2003 thirty-eight patients were diagnosed with anal cancer, 28 females and 10 males. The average age at diagnosis was 63.4 years. Age standardized incidence rates for anal cancer in Iceland were 0.3 (+/-0.2) of 100.000 males and 0.9 (+/-0.4) of 100.000 females. Most patients had squamous cell carcinoma (n=30). The remaining histologic types were malignant melanoma (n=3), adenosquamous carcinoma (n=1), adenocarcinoma (n=1), GIST (n=1) and undifferentiated carcinoma (n=2). The most common symptoms were rectal bleeding (n=27), mass lesion (n=28), pain (n=19) and pruritus (n=4). Most patients had more than one symptom. The duration of symptoms before diagnosis ranged from 2 weeks to 96 months (mean value 3.5 months). Treatment modalities used were chemotherapy (n=12), radiotherapy (n=25) and local excision (n=18) and/or APR (n=5). One patient received no treatment. Many patients were treated with more than one treatment modality (n=18). Twelve patients had recurrent cancer. The mean value of the time from diagnosis of the primary to the recurrent cancer was 15.6 months (range, 5.9-117). Sixteen patients remain with disease and ten have died of anal cancer. The five year survival rate for patients diagnosed in the years 1987 to 1998 is 75% but cancer-specific survival is 82%. CONCLUSION: Age-standardized incidence for anal cancer in ...